Escórias siderúrgicas e seus efeitos sobre a produtividade, qualidade industrial e resistência da cana-de-açúcar a doenças e à broca do colmo - Araújo, Leonardo Silva (2010)
The processes of smelting pig iron and steel produce large amount of slags and other wastes. These slags can be used in agriculture to correct soil acidity and/or as a source of silicon (Si), an element considered beneficial to plants. This study evaluated the effect of siderurgical slag Holcim on the sugar cane crop, compared to the certified slag Agrosilício® by parameters related to yield, industrial quality of the sugar cane and plant resistance to diseases and stem borer. Thus, a field experiment in Guaira Sugar Mill, Guaira-SP was done. The sugarcane variety SP80-3280 was grown in soil with three increasing doses of either Si source (400, 800 or 1600 kg ha-1) and a control treatment without application of any of the sources, in a randomized block design as a 2x3+1 factorial, resulting in seven treatments with four replications. Evaluations of plant tillers were done at 30, 60 and 90 days after planting and those of stem length were done 120 days after planting and at harvest. Analysis of leaf Si was done in samples collected 180 and 240 days after planting. Disease severity and the intensity of stem borer (Diatraea saccharalis) damage were done at harvest (after one year). It was observed that in the soil layer of 00-15 cm, Si concentration increased until the dose of 800 kg ha-1 of Holcin slag, while no effect was observed for either source in the other soil layers analyzed. The same effect was observed for leaf Si concentration, which remained unchanged with the application of either Si source to the soil. In contrast, the resistance of plants to diseases and to the stem borer increased when either source was applied up the dose of 800 kg ha-1 slag. The same dose effect was observed for yield. Although biometric parameters such as purity and fiber content of the juice were not affected by the silicate levels, POL and Brix of the juice were favorably affected by greater silicate doses, and at 1600 kg ha-1 Source 1 was better than Source 2. The use of slag dosed did not affect ATR (Total recoverable sugar); however, Source 1 was better than Source 2. The observed results show that similarly to Agrosilício® (Source 2), Holcim slag (Source 1) has high potential to be used in the cultivation of sugarcane, performing, for some variables, even better than the already certified Si source.